Interpersonal and self-regulation determinants of healthy and unhealthy eating behavior in adolescents - Kalavana, Theano; Maes, Stan; De Gucht, Veronique (My University, 2010)
The purpose of this study was to investigate the influence of interpersonal and personal factors on (un)healthy eating in adolescents. The study sample consisted of 473 adolescents. Regression analyses were conducted to examine the effect of family climate, peer influence and self-regulation cognitions (goal commitment, efficacy and ownership) on healthy and unhealthy eating. Self-regulation cognitions are positively related to healthy eating and negatively to unhealthy eating. We conclude that different aspects of family climate and peer influence are significantly related to both healthy and unhealthy eating. Interventions should be directed at self-regulation cognitions as well as at family and peer influence.
Keywords: Family climate; Healthy eating behavior; Peer influence; Self-regulation cognitions; Unhealthy eating behavior